Improve Creative Thinking Ability of Vector Material Through Problem Posing Type Pre Solution Posing at SMAN 3 Semarang - Tri Martini Nuhariyani (Urogram Studi Pendidikan Matematika, Universitas IVET, 2021)
In learning process, students often appear reluctant to read mathematics books. So that the students do not understand the meaning and concept of the material they have heard and recorded. This research offers a pre-solution posing type of problem posing model. Students make questions according to the situation given by the teacher and then it solve by themselves or finish them as discussion materials. The research objective is to examine, to describe the increase in creative thinking skills which have the effect of increasing learning achievement through the pre-solution posing type of problem posing model. The research was conducted at X-MIPA 2 SMAN 3 Semarang on vector material. Research variables are creative thinking skills and learning achievement. Data on creative thinking abilities were taken using observation sheets, data on learning achievement were taken by tests. The obtained data were scored, processed and presented descriptively. The results showed, the number of students completed, respectively, on the creative thinking variable was 57% and 86%, while the learning achievement was 60% and 91%. The increase that occurs shows the application of improved learning actions on vector material with the pre-solution posing type of problem posing learning model. Keywords: Creative Thinking, Pre Solution Posing, Learning Achievement, Problem Posing